Exploring the Redox Reaction Potential of Local Fruits: Galvani Cell Trials Based on Areca nut (Areca catechu), Rimbang (Solanum torvum), and Bangkok starfruit (Averrhoa carambola) - Fahmi, Jaman; Ramadhan, Dwi Sapri; Wardana, Dian; Safitri, Wulan Dwi; Mendrofa, Bulan Susanti; Br Nadeak, Stephani Bintang N.; ayumi, Sheilla Maliza; Nasution, Dhea Ananda; Zubir, Moondra; S, Abd Hakim (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
This research aims to explore the potential of three fruits, such as areca nut (Areca catechu), rimbang (Solanum torvum), and star fruit (Averrhoa carambola), as a natural electrolyte source in generating electricity through a simple Galvani cell test. The research method includes making Galvani cells using fruit pieces as electrolyte media, measuring the voltage and current produced, and testing the ability to light an LED as an indicator of electrical output. The measurement results showed that areca nuts produced the highest voltage and current compared to rimbang and star fruit, demonstrating its effectiveness as a natural electrolyte. This finding indicates that local fruits have the potential to be an environmentally friendly electrochemical energy source material that can be applied in education and simple technology. This research opens opportunities for further development in utilizing local biological resources for electrochemical applications.